Challenges of nurses in developing a palliative care innovation in Thailand: - Chongjarearn, Angkana; Cheumnok, Wuttipong (Thai Journal of Cardio-Thoracic Nursing, 2022)
Palliative care is the caring process which optimizes and mitigates the quality of patients’ life and families and releases pain including physically, mentally, and psychosocially especially last stage of patients’ lives. Palliative care emphasizes on the needs and wishes as main priority. Nurses who are part of the healthcare team obtain the highest expectations from patients and families due to the closeness and understanding their suffering. Nurses have the roles to provide empowering and mental support to patients and families in order to help them to cope problems appropriately. Nurses have to use knowledge’s, experiences and skills in inventing the innovative instruments responded to patients’ and families’ needs. It is challenge for nurses to develop palliative innovation that is appropriate and adaptable to the society changing environments where technological advancement and social constraints in living with COVID-19 pandemic. Nurses have to develop Artificial Intelligence (AI) and to use to care palliative patients for mobile health monitoring to improve the quality of care.